EFEKTIVITAS VARIASI LAMA PAPARAN SINAR ULTRAVIOLET - C TERHADAP PENURUNAN TOTAL KUMAN PADA ALAT MAKAN Di PANTRY PT. X (Politeknik Kesehatan Kemenkes Bandung, 2021)
Factors that affect the quality of food is the occurrence of food contamination by bacteria through unsanent tableware. Pt. X facilitates pantry as a place to eat for staff employees every break The requirement of the number of germs in cutlery is set at Permenkes No. 1096 year 2011 on Sanitary Hygiene Jasaboga which is 0 colonies/cm2 cutlery. The number of germs on the cutlery after the examination is 3.12 x 103 colonies/cm2 and exceeds the quality standard. Efforts to reduce the number of germs on the cutlery are carried out by radiation sterilization using ultraviolet light - c. This study aims to determine the effectiveness of long variations in exposure to UV-C rays to decrease the number of germs in the cutlery. This type of research is experimental research with pretest and posttest without control design. This type of research is experimentation. The population in this study is all cutlery in the Pantry and samples in this study are part of the cutlery in the Pantry. The test result after being given exposure to UV light for 10 minutes is 21 colonies/cm2, the duration of exposure 15 minutes is 4 colonies/cm2. And the exposure length is 20 minutes which is 0 colonies/cm2. Data analysis using One-Way Anova test with test results of pvalue 0.00 < 0.05 Obtained the effectiveness of long exposure in lowering the number of germs in the cutlery that is at the length of exposure 20 minutes obtained percentage of 100%. It is expected that sterilization cabinets can be used in the industry as a tool to kill the number of germs in cutlery.